2022
DOI: 10.3389/fphar.2022.903488
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Centre Prospective Study of the Efficacy and Safety of Alglucosidase Alfa in Chinese Patients With Infantile-Onset Pompe Disease

Abstract: Background: A high prevalence of infantile-onset Pompe disease (IOPD) in the Chinese population has been noted, but there are currently no reported clinical trials of enzyme replacement therapy (ERT) for IOPD in this population. The purpose of this study was to evaluate the efficacy and safety of alglucosidase alfa in Chinese patients with IOPD.Materials and Methods: A multicentre, single-arm, prospective, open-label clinical trial was performed at 4 sites in China. Eligible Chinese subjects with IOPD received… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…These data were also compared to the same historical controls, with survival at 24 and 36 months of 1.9% (95% CI: 0%–5.5%). Finally, the survival rate of Zhu et al ( 29 ) was 100% ( n = 9, 95% CI: 66.4%–100%).…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…These data were also compared to the same historical controls, with survival at 24 and 36 months of 1.9% (95% CI: 0%–5.5%). Finally, the survival rate of Zhu et al ( 29 ) was 100% ( n = 9, 95% CI: 66.4%–100%).…”
Section: Resultsmentioning
confidence: 84%
“…Therefore, we only considered the first to be published as its data were completed ( 26 ). Kishnani et al ( 16 ), Nicolino et al ( 28 ) and Zhu et al ( 29 ) showed the beneficial effect of ERT, with reductions in LV mass as follows: −106.6 g/m 2 ( 16 ), −62.7% ( 28 ) and −227.60 ± 155.99 g/m 2 ( 29 ), after ERT respectively.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…There are also references, however, that report the prevalence of severe allergic reactions with rhGAA in IOPD as low or absent. One of these is a research study that was conducted for a period of 52 weeks with 10 patients with IOPD who had received 20 mg/kg rhGAA biweekly; no severe adverse reactions were reported [ 17 ]. Another refers to an Italian expert panel review that states that approximately 1% of IOPD patients develop anaphylactic shock and/or cardiac arrest, while 5–14% of patients develop significant allergic reactions with rhGAA that involve at least two or three body systems [ 18 ].…”
Section: Discussionmentioning
confidence: 99%